Pre-clinical evaluation of clinically relevant iPS cell derived neuroepithelial stem cells as an off-the-shelf cell therapy for spinal cord injury - Dania Winn; Elias Uhlin; Elias Uhlin; Malin Kele; Ilse Eidhof; Ilse Eidhof; Anna Falk; Anna Falk (Frontiers Media S.A., 2024)
Preclinical transplantations using human neuroepithelial stem (NES) cells in spinal cord injury models have exhibited promising results and demonstrated cell integration and functional improvement in transplanted animals. Previous studies have relied on the generation of research grade cell lines in continuous culture. Using fresh cells presents logistic hurdles for clinical transition regarding time and resources for maintaining high quality standards. In this study, we generated a good manufacturing practice (GMP) compliant human iPS cell line in GMP clean rooms alongside a research grade iPS cell line which was produced using standardized protocols with GMP compliant chemicals. These two iPS cell lines were differentiated into human NES cells, from which six batches of cell therapy doses were produced. The doses were cryopreserved, thawed on demand and grafted in a rat spinal cord injury model. Our findings demonstrate that NES cells can be directly grafted post-thaw with high cell viability, maintaining their cell identity and differentiation capacity. This opens the possibility of manufacturing off-the-shelf cell therapy products. Moreover, our manufacturing process yields stable cell doses with minimal batch-to-batch variability, characterized by consistent expression of identity markers as well as similar viability of cells across the two iPS cell lines. These cryopreserved cell doses exhibit sustained viability, functionality, and quality for at least 2 years. Our results provide proof of concept that cryopreserved NES cells present a viable alternative to transplanting freshly cultured cells in future cell therapies and exemplify a platform from which cell formulation can be optimized and facilitate the transition to clinical trials.